Methanol poisoning induced chronic neurological sequelae - Kaur, Amolpreet; Chandey, Manish; Singh, Parminder (International Journal of Research in Medical Sciences, 2024)
Acute methanol intoxication can have serious neurological sequelae which can entail the course of illness. Patients generally present with acute neurological, visual, and gastrointestinal symptoms. Here we present a case of methanol poisoning who developed profound vision loss and severe brain damage with characteristic bilateral necrosis of the putamen shown on magnetic resonance imaging. This study highlights a unique undiagnosed case report of blindness associated with extrapyramidal symptoms, which was later found to be associated with methanol poisoning. A high index of suspicion is required for timely management of such cases, to prevent the long-term neurological sequelae.